Socialization Skills and Cooperative Games During The Pandemic: An Experimental Study on Students Having Slow Development of Communication - Haris Herdiansyah; Dindin Dimyati (CoverAge: Journal of Strategic Communication, 2023)
Children are affected by the Covid-19 pandemic, which has lasted nearly three years. The pandemic condition, which requires everyone to stay at home and interact at home, has a negative impact on the development of children's social interactions, particularly their socialization skills. It was discovered that there was a delay in the development of children's socialization due to hampered social learning processes, lack of direct social interaction, lack of social stimulation, and so on, causing children to grow up as individuals who were shy, inferior, and lacked social confidence, necessitating an intensive effort to accelerate their socialization skills so that children's mental development is not hampered, and they can re-adapt to their peers. The experimental design used was a two-sample pre-test-post-test design, with all respondents divided into experimental and control groups. Purposive sampling was used in this study. A socialization skills questionnaire was used as the research instrument. Pearson's alpha was used for validity tests, and Cronbach's alpha was used for reliability tests. Multiple regression was used in hypothesis testing. The data analysis revealed that the difference between pre-test and post-test scores had a t-value of 5.079 and a probability value (sig. 2-tailed) of 0.000 (P0.01) . This finding indicates a difference in socialization skills between KE and KK.